The Use Of Project Based Learning In Pancasila Student Profile To Improve Speaking Skill (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2024)
Speaking skill is a crucial aspect of learning a foreign language, especially English. However, many students struggle with English due to various challenges. Improving students' speaking skills and strengthening the Pancasila student profile can be achieved through various methods. One effective method is Project-Based Learning (PjBL). This research aims to explain the speaking skills of XI-C class students before and after implementing project-based learning and to find out the effect of project based learning to the Pancasila student profile. This research conduct at SMAN 1 Kediri, the study used a quantitative approach, specifically a pre-experiment with a single group pre-test and post-test design. The research involved 36 students from class XI-C. Data collection included pre-test and posttest assessments, and data analysis was performed using paired t-tests in IBM SPSS Statistics. The results indicate that PjBL significantly improves students' speaking skills in all aspects while also strengthen the Pancasila student profile. In conclusion, PjBL is an effective method for enhancing students' speaking skills.